2007
DOI: 10.1063/1.2781392
|View full text |Cite
|
Sign up to set email alerts
|

Single and dual beam optical switching of resonance energy transfer

Abstract: Through photonic mechanisms based on near-field coupling, laser radiation can engage with resonant energy transfer in a variety of suitably designed materials and molecular structures. Energy that has been acquired, through the initial absorption of resonant laser light, undergoes transfer between chromophores only on the throughput of off-resonant light, the process known as laser-assisted resonance energy transfer. The comprehensive results that are presented here extend and generalize the theory for both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…This condition requires the transition dipole moments of the donor and acceptor, and their mutual displacement vector, to be mutually perpendicular-thus excluding a Förster process that would otherwise be possible on symmetry and energetic grounds. 48 By application of the off-resonant laser beam the transfer of energy is activated, effecting all-optical switching action.…”
Section: Introductionmentioning
confidence: 99%
“…This condition requires the transition dipole moments of the donor and acceptor, and their mutual displacement vector, to be mutually perpendicular-thus excluding a Förster process that would otherwise be possible on symmetry and energetic grounds. 48 By application of the off-resonant laser beam the transfer of energy is activated, effecting all-optical switching action.…”
Section: Introductionmentioning
confidence: 99%
“…an overall process whose quantum amplitude is determined by third-order perturbation theory. Similar effects occur in connection with resonance energy transfer, as numerous studies have shown; [29][30][31][32][33][34][35][36][37][38] nonetheless in contrast to the perturbations that can be brought into effect by a static field, the leading orders of which arise in second-order, i.e. linear in both the emitted and the applied field.…”
Section: Laser-controlled Fluorescencementioning
confidence: 78%
“…It has been suggested that these and other principles concerning the effect of static electric fields on coupled quantum dots may have an important role to play in quantum logic applications. Andrews has recently proposed a system in which the simultaneous delivery of laser pulses, with two differing off-resonant frequencies, might achieve a similar purpose, 101,102 while other studies currently underway are beginning to explore novel nanomechanical effects produced by the action of RET. 103 …”
Section: Developing Applicationsmentioning
confidence: 99%